Scale problem in capital market research / Iraj Asghari and Azam Mohtadi - Asghari, Iraj; Mohtadi, Azam (Institute of Research Management Innovation (IRMI), 2015)
This paper is a review and aims to present and interpret the results of previous research carried out in the context of reducing the problems associated with '(scale effects " in capital market research. Evaluating the results of investigations in the field shows that deflating all the elements of the regression model using suitable deflator is the preferred approach of dealing with scale problem in research. However, there is no agreement among researchers on the best deflator and studies on scale effect sought to be continued.